Low-Grade Adenosquamous Carcinoma of the Axilla of Breast Origin in a Male: A Case Report and Literature Review - Yan, Xingqiang; Zhu, Fanshuang; Wang, Qiupeng; Chen, Lijie; Zhou, Yixing; Wu, Zenggui; Mei, Linhang; Ma, Zhaosheng; Cui, Binbin; Cao, Feilin (Frontiers in Oncology, 2020)
Low-grade adenosquamous carcinoma (LGASC) is a rare invasive tumor that occurs in breast parenchyma. It has previously only been reported in females. Herein, we describe the case of a 52-year-old male who presented with a palpable mass in his right axilla that he reported had been present for 20-years. This is the first report of a male patient with LGASC. Core needle biopsy pathology revealed a benign mass of mammary origin, but its type was initially misdiagnosed. It was only correctly identified via postoperative pathology after local excision, which indicated that the mass exhibited the typical pathological characteristics of LGASC. Immunohistochemical analysis revealed positive expression of estrogen receptor, which was inconsistent with the typical “triple-negative” immunophenotype of LGASC. After resection of the mass the patient was advised to participate in regular outpatient follow-up. In conclusion, LGASC should be considered in male patients with a mass lesion in their breast or axilla, even when core needle biopsy indicates a benign mass of breast origin. One-stage local resection is recommended for the treatment of male patients with LGASC, but it is crucial to ensure that the margins are negative and postoperative adjuvant radiotherapy is not recommended.